Correlations Between Intratumoral Microvessel Density and Histopathological Type or Neoadjuvant Radiotherapy for Rectal Carcinoma - DUMITRESCU, T. (Curr Health Sci J, 2015)
Purpose: This study aims to evaluate intratumoral microvessel density in rectal carcinoma cases with different histopathological type (adenocarcinoma and mucinous carcinoma) and different preoperatory neoadjuvant radiotherapy status (irradiated / non-irradiated) ,thus analyzing any possible statistical correlation between these parameters. Material and methods: Our prospective study consists in standard immunohistochemistry procedures using CD34, CD31 and CD105 antibodies, which were performed on 25 samples of rectal carcinoma, in order to determine intratumoral microvessel density. Results: The 25 case study group was divided either by histopathological type or by prior radiotherapeutical treatment as follows: 9 cases of mucinous carcinoma versus 16 cases of adenocarcinoma and 13 cases of rectal cancer that have not received neoadjuvant radiotherapy versus 12 cases of rectal cancer with preoperatory radiotherapy. Conclusions: The number of intratumoral microvessels is higher in non-irradiated rectal tumors and in adenocarcinomas, this remark being statistical significant (with only one exception – CD34 staining in non-irradiated versus irradiated tumors) for all types of vessels (new-grown and mature). This result is due to the benefic effect of neoadjuvant radiotherapy on decreasing angiogenic activity, thus having an important prognostic value for rectal cancer.